"Everyone Needs to Be Cared For": Exploring Care from the Perspective of Prison Officers Working with Young Adult Offenders. Issue 1 (1st January 2022) - Frost, Laura; Scott, Helen; Mia, Abdullah; Priest, Helena
ABSTRACT: The purpose of the current study was to explore the care related experiences of prison officers working on an Offender Personality Disorder (OPD) Pathway service, located within a prison for young adults. Due to the exploratory nature of the study, a qualitative, grounded theory approach was utilized. Individual semi-structured interviews were conducted with twelve officers. The data were analyzed in accordance with constructionist grounded theory methodology. The results identified the core category of relationships and two additional categories: impact of caring and development of officers' caring approach. These categories were integrated into a model of care. Officers reported caring to be both rewarding and challenging. They expressed beliefs that providing care to service users increases wellbeing and reduces recidivism. The results demonstrate a reciprocal nature to care, with officers needing to receive care themselves in order to care effectively for service users. Officers' approach to caring for service users was dependent upon an interaction between their own experiences of care, care related values, their relationship with individual service users and their own emotional state. Individual officers and the OPD Pathway service could benefit from additional support and understanding from the prison system.